Sanders 제 III형 종골 골절에서 최소침습 족근동 접근법과 광범위 외측 접근법 간 정복 정도 비교 - 김종은; 이건우; Jong-Eun Kim; Gun-Woo Lee (대한족부족관절학회지, 2025)
Purpose: This study compared the quality of reduction between the minimally invasive sinus tarsi approach (STA) and the extensile lateral approach (ELA) for Sanders type III calcaneal fractures, using postoperative computed tomography (CT) and plain radiographs. Materials and Methods: Sixty-five patients (71 cases) with Sanders type III calcaneal fractures treated with an open reduction and internal fixation using STA (38 cases) or ELA (33 cases) between January 2015 and December 2020 were reviewed retrospectively. The Böhler's and Gissane's angles were measured on the final follow-up weight-bearing lateral radiographs. The reduction quality of the posterior facet was assessed using semi-coronal CT images taken at least 6 months postoperatively and classified as excellent, good, fair, or poor based on the step-off and gap. Results: The mean Böhler's angle in the STA and ELA groups was 25.6° and 27.0°, respectively (p=0.538). The mean Gissane's angle in the STA and ELA groups was 116.7° and 120.0°, respectively (p=0.168). The CT evaluation of posterior facet reduction showed excellent or good results in 23 fractures (60.5%) in the STA group and in 29 fractures (87.9%) in the ELA group, showing a significant difference favoring ELA (p=0.018). Conclusion: Plain radiographic parameters showed no significant difference between the two approaches. On the other hand, CT-based assessment revealed that ELA achieved superior posterior facet reduction compared to STA in Sanders type III calcaneal fractures. Hence, ELA may be more effective in achieving anatomic reduction in Sanders type III calcaneal fractures.